2021
DOI: 10.33774/chemrxiv-2021-njqc8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Special feature of COVID-19 in FMODB: Fragment molecular orbital calculations and interaction energy analysis of SARS-CoV-2 related proteins

Abstract: SARS-CoV-2 is the causative agent of coronavirus(known as , the virus causing the current pandemic. there are ongoing researches to develop effective therapeutics and vaccines against COVID-19 using various methods, and many results have been published.The structure-based drug design of SARS-CoV-2 related proteins is promising. However, 2 reliable information regarding the structural and intra-and intermolecular interactions is required. We have conducted studies based on the fragment molecular orbital (FMO) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The contributions of the interactions were not only electrostatic interactions and hydrogen bonds but also π-orbital interactions (π-π, CH/π, NH/π, OH/π, and lone pair/π), halogen bonds, and interactions unique to quantum chemical calculations 26,35,36 . Compared to our previous results 21 of clustering the FMO-based interaction energies between 110 ligand complex structures registered by PDB, ensitrelvir more effectively utilizes multiple pockets of S1', S1, and S2 in its molecular recognition to M pro . It also confirmed that ensitrelvir acquired more amino acid residues and interactions than GC376 (PDB ID: 6WTT, FMODB ID: 4NVVN) 27,29 , a well-known covalent inhibitor of animal anticoronaviruses.…”
Section: New Insights Into Analysis Of Interaction Energies In Sbddmentioning
confidence: 54%
See 1 more Smart Citation
“…The contributions of the interactions were not only electrostatic interactions and hydrogen bonds but also π-orbital interactions (π-π, CH/π, NH/π, OH/π, and lone pair/π), halogen bonds, and interactions unique to quantum chemical calculations 26,35,36 . Compared to our previous results 21 of clustering the FMO-based interaction energies between 110 ligand complex structures registered by PDB, ensitrelvir more effectively utilizes multiple pockets of S1', S1, and S2 in its molecular recognition to M pro . It also confirmed that ensitrelvir acquired more amino acid residues and interactions than GC376 (PDB ID: 6WTT, FMODB ID: 4NVVN) 27,29 , a well-known covalent inhibitor of animal anticoronaviruses.…”
Section: New Insights Into Analysis Of Interaction Energies In Sbddmentioning
confidence: 54%
“…Therefore, in this study, we evaluated the interaction energy between the inhibitor and M pro based on quantum chemical calculations using the fragment molecular orbital (FMO) method [8][9][10][11] to investigate the physicochemical factors that enhanced the inhibitory activity in the drug design from this compound 1 to ensitrelvir. Inter-fragment interaction energy (IFIE) analysis based on FMO calculations can identify amino acid residues and functional groups vital for binding proteins and their inhibitors [12][13][14][15][16][17][18][19][20][21] . Furthermore, by the energy decomposition analysis of IFIE, the type and contribution of the interaction can be clarified for electrostatic interaction (ES), exchange repulsion (EX), charge transfer interaction (CT), and dispersion force interaction (DI) [22][23][24][25] .…”
Section: Toc Graphicsmentioning
confidence: 99%
“…Proteins form a very important class of compounds of paramount importance for biochemistry. Protein structures are indispensible to drug discovery, including SARS-CoV-2-related research . Although several experimental methods exist for determining protein structure, such as nuclear magnetic resonance (NMR) and X-ray crystallography, collected experimental data are subject to modeling simulations to produce a structure, and due to resolution limitations and crystal disorder, the resulting structure may have missing atoms or atoms with uncertain or inaccurate coordinates.…”
mentioning
confidence: 99%